Barriers and facilitators to implementation of a home-based cardiac rehabilitation programme for patients with heart failure in the NHS: a mixed-methods study - Rod S Taylor; Paulina Daw; Samantha B van Beurden; Jet J C S Veldhuijzen van Zanten; Alexander Harrison; Sinead T J McDonagh; Patrick J Doherty; Colin J Greaves; Hasnain M Dalal; Grace E R Wood (BMJ Open)
Objectives This study aimed to identify barriers to, and facilitators of, implementation of the Rehabilitation EnAblement in CHronic Heart Failure (REACH-HF) programme within existing cardiac rehabilitation services, and develop and refine the REACH-HF Service Delivery Guide (an implementation guide cocreated with healthcare professionals). REACH-HF is an effective and cost-effective 12-week home-based cardiac rehabilitation programme for patients with heart failure.Setting/participants In 2019, four early adopter ‘Beacon Sites’ were set up to deliver REACH-HF to 200 patients. In 2020, 5 online REACH-HF training events were attended by 85 healthcare professionals from 45 National Health Service (NHS) teams across the UK and Ireland.Design Our mixed-methods study used in-depth semi-structured interviews and an online survey. Interviews were conducted with staff trained specifically for the Beacon Site project, identified by opportunity and snowball sampling. The online survey was later offered to subsequent NHS staff who took part in the online REACH-HF training. Normalisation Process Theory was used as a theoretical framework to guide data collection/analysis.Results Seventeen healthcare professionals working at the Beacon Sites were interviewed and 17 survey responses were received (20% response rate). The identified barriers and enablers included, among many, a lack of resources/commissioning, having interest in heart failure and working closely with the clinical heart failure team. Different implementation contexts (urban/rural), timing (during the COVID-19 pandemic) and factors outside the healthcare team/system (quality of the REACH-HF training) were observed to negatively or positively impact the implementation process.Conclusions The findings are highly relevant to healthcare professionals involved in planning, delivering and commissioning of cardiac rehabilitation for patients with heart failure. The study’s main output, a refined version of the REACH-HF Service Delivery Guide, can guide the implementation process (eg, designing new care pathways) and provide practical solutions to overcoming common implementation barriers (eg, through early identification of implementation champions).